2021
DOI: 10.1021/acssuschemeng.1c02493
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Cathodes from Spent Lithium-Ion Batteries Based on the Selective Extraction of Lithium

Abstract: The demand for lithium-ion batteries (LIBs) has risen dramatically over the years. However, many of the essential component elements in cathodes, such as cobalt and lithium, are both costly with limited resources. Therefore, the recycling of spent LIB cathodes is of great significance to conserving resources and the environment. In this work, we reported a novel metal-based strategy to selectively leach lithium from different types of cathodes (NCM, LCO, and LMO) by Co2+ or Mn2+, which can realize over 95% lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…As seen in Table S5, the lithium contents are further reduced from 0.52 to 0.01 during Stage II, while the ratio of M elements in R-200-18 has been restored to be the original value of S-NCM, which demonstrates the ion exchange reaction between Li + and M ions during Stage II. Our recent work has also confirmed that M 2+ can exchange with Li + from LiMO 2 following the charge balance principle under a M/Li ratio of 0.5 . In the case of stoichiometric H 2 SO 4 as the leaching reagent, part of Li + and M 2+ were first dissolved out from LiMO 2 by H + , while the released M 2+ would then exchange with the rest of the Li + from the remaining cathodes.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…As seen in Table S5, the lithium contents are further reduced from 0.52 to 0.01 during Stage II, while the ratio of M elements in R-200-18 has been restored to be the original value of S-NCM, which demonstrates the ion exchange reaction between Li + and M ions during Stage II. Our recent work has also confirmed that M 2+ can exchange with Li + from LiMO 2 following the charge balance principle under a M/Li ratio of 0.5 . In the case of stoichiometric H 2 SO 4 as the leaching reagent, part of Li + and M 2+ were first dissolved out from LiMO 2 by H + , while the released M 2+ would then exchange with the rest of the Li + from the remaining cathodes.…”
Section: Resultssupporting
confidence: 62%
“…Our recent work has also confirmed that M 2+ can exchange with Li + from LiMO 2 following the charge balance principle under a M/ Li ratio of 0.5. 24 In the case of stoichiometric H 2 SO 4 as the leaching reagent, part of Li + and M 2+ were first dissolved out from LiMO 2 by H + , while the released M 2+ would then exchange with the rest of the Li + from the remaining cathodes. It is worth noting that the reactions involved are also subject to the charge balance principle, suggesting the selective extraction of Li + from LiMO 2 and formation of the MOOH phase under a H/Li ratio of 1.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, waste LIBs are rich in lithium, cobalt and other resources, and their recycling is especially closed-loop. Recycling can alleviate environmental pollution while alleviating resource shortages. Therefore, the closed-loop metal recycling technology for spent LCO batteries has received extensive attention …”
Section: Introductionmentioning
confidence: 99%
“…7 In contrast, cathodic LFP materials have the highest economic value, i.e., approximately 69% that of the whole battery. 8 However, the complex reclamation of Li salt from spent LFP through conventional hydrometallurgical treatments 9,10 based on combinations of leaching reagents (e.g., H 2 SO 4 or organic acid with H 2 O 2 ) 11,12 and precipitants (e.g., Na 2 CO 3 ) 13 hinders a 100% recovery, and it is also not economically or environmentally feasible enough to recycle because large quantities of chemical reagents and energy will be consumed for the resynthesis of new LFP cathodes. In summary, the lack of graphite recycling strategies and drawbacks of hydrometallurgy warrant a facile strategy that directly regenerates spent LFP cathodes and repurposes spent anodic graphite.…”
Section: Introductionmentioning
confidence: 99%
“…, approximately 69% that of the whole battery. 8 However, the complex reclamation of Li salt from spent LFP through conventional hydrometallurgical treatments 9,10 based on combinations of leaching reagents ( e.g. , H 2 SO 4 or organic acid with H 2 O 2 ) 11,12 and precipitants ( e.g.…”
Section: Introductionmentioning
confidence: 99%